Minimal Open Access Ileocolic Resection in Complicated Crohn's Disease of the Terminal Ileum. (28th February 2020) - Sica, Giuseppe S.; Di Carlo, Sara; D'Ugo, Stefano; Arcudi, Claudio; Siragusa, Leandro; Fazzolari, Laura; Biancone, Livia; Monteleone, Giovanni; Cardi, Maurizio; Sibio, Simone
Abstract : The objective of this study was to evaluate the possibility to undertake an ileocolic resection in complex Crohn's disease using a minimal open abdominal access using standard laparoscopic instruments. The incision was carried out over the previous McBurney scar, with a mean length of 6 cm. Seventy-two patients with complicated Crohn's disease underwent IC resection in the considered period; 12 patients had a McBurney scar due to a previous appendectomy and represented the group of study. Feasibility and safety of the procedure were evaluated. Clinical data and outcome were compared with a control arm of 15 patients who had a standard laparoscopic IC resection, pooled out from our database among those who had a McBurney incision as service incision. Mean operative time and postoperative stay were significantly shorter in the study group. Blood loss and operative costs were also lower in the study group but did not reach statistical significance. Minimal open access ileocolic resection (MOAIR) through a small McBurney incision seems safe and feasible in complex Crohn's disease. Some advantages over standard laparoscopic surgery could be found in surgical outcomes and costs.